Sistem Informasi Monitoring dan Evaluasi Proyek dengan Menerapkan Perhitungan Deviasi - Sunarya, Muhammad Hendra; Irwansyah, Rusman; Pebriadi, Muhammad Syahid (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2020)
The process of monitoring and evaluating a project needs to be done to ensure the project runs smoothly. The problems that arise at this stage are obstacles to knowing the progress of the ongoing project. Some other obstacles are the potential for file loss, duplication of data, human errors, the need for fast processing, and the need for data integrity of two systems. This study aims to develop a project monitoring and evaluation information system applying deviation calculations. This calculation is carried out to see the realization of the work of an ongoing project. The system design technique uses the use case diagram method which describes the process of the system. The waterfall method is used to develop a monitoring and evaluation information system for this project. The research result is in the form of a project monitoring and evaluation information system that can provide information about the work realization of an ongoing project.